Anticancer properties of berberine - analysis of the latest reports - Rozwadowska, Patrycja; Bator, Piotr; Razik, Michał; Ramian, Jan; Rybak, Jakub; Magiera, Barbara; Magiera, Karol; Razik, Wiktor (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Berberine is a plant alkaloid that naturally occurs in the fruits of common barberry (Berberis vulgaris). This alkaloid has long been used in natural medicine. It exhibits a range of bioactivities, such as antioxidant, anti-inflammatory, antidiabetic, anti-edema, and antimicrobial actions. Through the promising therapeutic effects of berberine in metabolic syndrome, as well as its impact on carcinogenesis, this compound is beginning to play a significant role in preventive medicine. Recently, particular attention has been paid to the anticancer properties of berberine, which are based on many biochemical pathways, particularly its pro-apoptotic and anti-inflammatory action. The study aimed to review the anticancer mechanisms of berberine and summarize them about individual cancers. State of knowledge: The article reviews the current literature on the anticancer properties of berberine for individual cancers, focusing primarily on its molecular mechanisms of action. In addition, the potential of berberine as a promising candidate forming the basis for drug production and its use in preventive medicine was analyzed. Summary: In summary, many studies have shown that berberine exhibits anticancer activity in many types of cancers, including breast, lung, stomach, liver, colorectal, ovarian, cervical, and prostate cancers. Berberine inhibits the growth of cancer cells, limits metastases, induces apoptosis, stimulates autophagy, and enhances the effectiveness of anticancer drugs. Despite its potential as a promising candidate for drug production, there are currently no approved pure berberine preparations for the treatment of specific ailments. Research on its effectiveness and safety is still ongoing.